ANALYSIS OF EMPLOYMENT OPPORTUNITY DETERMINANTS IN WEST JAVA: STUDY PERIOD 2010-2023 - Khoiriyah, Nikmatul; S, Ririt Iriani (Universitas 17 Agustus 1945 Surabaya, 2025)
Regional economic development is closely related to the ability of a region to create employment opportunities that support the welfare of its population. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), population, average length of schooling (RLS), and Provincial Minimum Wage (UMP) on employment opportunities in West Java Province during the period 2010–2023. Using a quantitative approach with time series data analysis, this research applies multiple linear regression with SPSS to test the influence of the independent variables on employment opportunity levels. The classical assumption tests indicate that the regression model is free from problems of normality, multicollinearity, autocorrelation, and heteroscedasticity. The results show that population and average length of schooling have a significant and positive effect on employment opportunities, implying that increasing population drives demand for goods and services which in turn stimulates job creation, while higher education improves workforce skills and competitiveness. Conversely, GRDP and UMP do not show a significant influence on employment opportunities, suggesting that economic growth and wage levels are not automatically aligned with job creation, especially in capital-intensive sectors. The findings of this study provide empirical insight into the determinants of employment opportunities and offer policy recommendations for addressing unemployment and improving labor market absorption in densely populated regions like West Java.